Educational outcomes of children with cerebral palsy - Jones, Hywel; Carter, Bethan; Bethan, Jackie; Collins, Huw; Wang, Ting; Rees, Sarah; Kemp, Alison; Paranjothy, Shantini (International Journal of Population Data Science, 2018)
Introduction Children with special educational needs (SEN) are more likely to have disadvantaged backgrounds than their peers, attend school less and do not achieve as well academically. Many children with a cerebral palsy (CP) have SEN but little is known about their educational outcomes. Objectives and Approach To investigate the background of children in Wales with CP and describe their educational experience including: type of SEN and SEN provision; school attendance; achievement—teacher assessments at the end of the Foundation Phase and Key Stages 2 and 3 of the National Curriculum (NC)— and in General Certificate of Secondary Education (GCSE) examinations. Data from the Pupil Level Annual School Census (PLASC), NC and GCSE results were linked with routine e-health records of primary and secondary health care data held in SAIL. Using health care records for everyone aged between 0-25 in 2004–14, cases of CP were flagged. Results The linked data set included some 1500–2000 children per school census classified as having a CP, representing a prevalence of some 0.3%. Provisionally, results show: prevalence of CP is higher amongst children living in relatively deprived areas; around 60% of CP children have a statement of SEN; the SEN type most commonly recorded for CP children with SEN is ‘Physical and medical difficulties’ and relatively high proportions have profound, multiple or severe learning difficulties; around 30% of CP children are educated in special schools; CP children in main stream (primary, middle and secondary) schools tended to miss more school sessions (~50% more) than other children and lower percentages achieved the expected levels at key stages 2 and 3 and the Level 2 GCSE threshold. Conclusion/Implications This work demonstrates the utility of record-linkage for providing information to parents, carers and policymakers about education outcomes for this group of children to inform planning and service provision.